Morbidity profile and immediate outcome of low birth weight neonates in a rural tertiary care hospital of Gujarat, India - Rasania, Manish; Pathak, Sunil; Dogra, Prerna; Jain, Ayushi; Shah, Neil; ., Shivanand (International Journal of Contemporary Pediatrics, 2018)
Background: Low birth weight (LBW) has been defined as a birth weight of <2.5 kilogram regardless of gestational age. In India, every 3rd born child is of LBW. LBW is associated with increased neonatal mortality and morbidity, compromised growth and cognitive development. Methods: This is a retrospective cohort study using previously collected data from January 2015 to December 2015. Results: Out of 1238 live births, 485 (39.17%) were LBW. 456(94.01%) were LBW weighing >1500 grams (LBW), 22(4.53%) were VLBW, and 07(1.44%) were ELBW. 361(74.43%) were LBW2 (birth weight ≥2000 - <2500 grams), 95(19.58%) were LBW1 (birth weight ≥1500 - <2000 grams). 289(59.58%) of LBW neonates were full term. SNCU admission is significantly higher in LBW neonates (25.8% vs 9.61%). Morbidities were higher in LBW neonates compared to normal birth weight neonates. Difference was more significant in incidence of sepsis (3.72% vs 0.83%), RDS (2.19% vs 0%), TTN (5.48% vs 2.36%), hypoglycemia (1.31% vs 0%), feed intolerance (1.09% vs 0%) and risk of major congenital malformation (1.97% vs 0.27%). Need for respiratory support was 4.82% in LBW vs 2.36% in normal birth weight neonates. Morbidities were significantly higher in VLBW and ELBW neonates. Immediate poor outcome was in 3.92% in LBW neonates, while it was 0.56% in normal weight neonates. Poor immediate outcome was 1.11% in LBW2, 2.10% in LBW1, 10% in VLBW1, 41.66% IN VLBW2, and 100% in ELBW. Conclusions: LBW neonates are at higher risk of morbidities and mortalities. The major determinant for mortality in LBW babies is the birth weight. The best option to prevent LBW is by improving maternal health. Improvement of perinatal and neonatal services in government sector and public private partnership model of free neonatal care can help to achieve the INAP goal of NMR <10 by 2030.